Android-Based Text Message Encryption and Decryption Application Using the Advanced Encryption Standard Algorithm - Putra, Riski Adi; Yupianti, Yupianti; Prasetyo R, Eko (Jurnal Media Computer Science, 2023)
Kaur 2 Public High School is one of the State Senior High Schools in Kaur District, Bengkulu Province. Communication between teachers or teachers and students or students and students has so far been carried out through text message applications that are already available on users' smartphones so that they exchange information. However, the information sent has not been fully implemented by security, where the message sent is the original message, and the recipient of the original message can read it immediately. This of course makes it easier for certain parties who intend to get the message. An android-based text message encryption and decryption application using the Advanced Encrytion Standard algorithm was created to help maintain security of communication between senders and recipients so that confidentiality is maintained. This application was created using Android Studio and has installed the JSON web service, so that it can be accessed by Android smartphone devices with the internet. Messages that have been sent will be stored in the MySQL database in the form of scrambled records, so it is necessary to do encryption to find out what the contents of the message are, where the Advanced Encryption Standard Algorithm is cryptography that uses symmetric keys (encryption and decryption keys must be the same). Based on the results of the tests that have been carried out, the functionality of the android-based text message encryption and decryption application at SMA Negeri 2 Kaur runs well as expected and the message sent between the recipient and the sender is kept confidential because the message is encrypted.